TEO-SOSIOLOGI SEBAGAI BASIS MODERASI BERAGAMA DI TENGAH PANDEMIK COVID 19 - Muhtador, Moh (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2021)
In early 2020, the world was shocked by the outbreak of the corona virus (covid 19) that emerged in Wuhan, China and quickly spread to the rest of the world, including Indonesia. The pandemic that occurred in Indonesia tested citizens who are known to be multicultural with religion, language, culture, religion, ethnicity and race from the aspect of spirituality (divinity) and social (humanity), because covid 19 does not look at social and religious strata. Therefore, it is necessary to read religious moderation as a discourse in multicultural life in Indonesia as a mainstream in growing spirituality and social life. This article is a qualitative literature study with techniques for collecting data from several sources such as online news, journal articles and phenomena related to religious issues and COVID-19 which are analyzed with Islamic theological theory and sociology, to get a comprehensive reading of moderation. religion during a pandemic. First, theologically it is believed that God is the center of the cosmos which is to grow faith with the representation of the Spirit and can interpret theology inclusively. Second, in the context of Indonesia, it is sociologically aware that the spread of religion is not carried out by means of violence and that religion and culture act as social capital.